Weathering of coals from the Waterberg and Limpopo Coalfields, South Africa - Sebola, Mandy-Jane Tlou (My University, 2018)
This study investigated the effects of weathering on coal from the Waterberg and Limpopo Coalfields with the aim to understand how the quality of these coals changed during the early stages of oxidative weathering under dry and wet conditions. Coal was sampled from freshly exposed seams in both coalfields to provide, as best as possible, an un-weathered parent sample from which the extent of weathering could be determined. The Middle Seam was sampled from the Limpopo Coalfield whereas Benches 3, 5, 9B and 11 were sampled from the Waterberg Coalfield. This suite of samples enabled investigation into the impact of weathering on coals with similar properties but originating from different localities (Waterberg Coalfield vs Limpopo Coalfield), as well as coal with different properties originating from the same locality (Benches 3, 5, 9B and 11). Furthermore, the impact of weathering was studied on the coking properties (Middle Seam vs Bench 3) and heating properties using thermal coal (Bench 5). The experiment was conducted over a duration of six months during which a subset of the samples from each coalfield was kept dry in perforated containers, whilst the remaining samples were frequently watered to simulate the effect of rainfall under controlled settings. The particle size of the samples was reduced to -1mm to enhance the surface area for a more rapid reaction. Thereafter the samples were left to weather outdoors, on the roof of a building at the University of the Witwatersrand, Johannesburg. The average temperature conditions affecting the samples during the research period ranged between 9.40-27.23 °C. Several conventional coal analyses (proximate analysis, ultimate analysis, coal petrography, XRF & XRD) were used in conjunction with advanced techniques (EMPA, FE-SEM & Raman spectroscopy) to detect early signs of weathering on the organic and inorganic coal constituents. The impact of weathering on technological properties of the coal samples were investigated using calorific value, thermogravimetry and free swelling index. After six months of weathering, very small changes were observed in the coal quality due to weathering. The chemical and petrographic composition of the coals remained relatively unaffected by weathering, whereas the mineral matter and swelling properties of the coals were more susceptible to weathering under wet conditions. The alteration of minerals was more evident in the samples that were watered throughout the experiment, irrespective of their original locality. These samples were characterized by the precipitation of gypsum on the surface of the wet coals, as well as the appearance of red calcite grains. Analysis of the red calcite grains revealed rare growth rims associated with the precipitation of siderite. Although the findings of the thermogravimetric analysis suggested that the reactivity of the thermal coal had been slightly reduced by weathering (especially by weathering under wet conditions), the CV trend for this coal did not appear to be impaired. Hence, the effect of weathering on the heating properties of this sample are inconclusive. Ultimately, after 6 months of exposure to weathering the quality of the coals remained very similar to their fresh parent samples. However, the swelling properties of the coking coals from each coalfield were diminished. Therefore, caution is advised for the stockpiling of the coking coals outdoors, which should not exceed longer than 4-6 months, especially in the case of the Waterberg coking coal.
A dissertation submitted in fulfilment of the degree of Master of Science in Geology in The Faculty of Science at the University of the Witwatersrand, Johannesburg. 31 May 2018
Keywords: Coal-weathering; Coal--Combustion